Association between the coexistence of premorbid sarcopenia, frailty, and disability and functional outcome in older patients with acute stroke. Issue 8 (18th July 2022) - Nozoe, Masafumi; Noguchi, Madoka; Kubo, Hiroki; Kanai, Masashi; Shimada, Shinichi
Abstract : Aim: To investigate the effects of coexisting conditions such as premorbid sarcopenia, frailty, and disability on functional outcomes in older patients with acute stroke. Methods: This prospective cohort study included older patients (aged ≥65 years) hospitalized for acute stroke at a single neurosurgical hospital. Premorbid sarcopenia, frailty, and disability were diagnosed using the strength, assistance with walking, rising from a chair, climbing stairs, and falls (SARC‐F) questionnaire, frailty index, and modified Rankin Scale (mRS) on admission. The primary outcome was the mRS score 3 months after stroke, and a poor outcome was defined as mRS ≥4. Results: This study included 317 older patients with acute stroke (median [interquartile range] age: 76 [12] years). Premorbid sarcopenia, frailty, and disability (mRS = 2 or 3) were identified in 59 (19%), 27 (9%), and 54 (17%) patients, respectively. Two coexisting conditions were observed in 26 patients (8%), and three were observed in 18 patients (6%). Adjusted logistic regression analysis revealed that coexisting conditions were independently associated with poor outcomes (one condition, adjusted OR: 3.20 [95%CI: 0.98–10.45]; two conditions, adjusted OR: 6.57 [95%CI: 1.74–24.87]; three conditions, adjusted OR: 12.70 [95%CI: 2.65–60.91]). Conclusions: The coexistence of premorbid sarcopenia, frailty, and disability was associated with poor functional outcomes in older patients with acute stroke. Geriatr Gerontol Int 2022; 22: 642–647 .